Pembangunan Bandar Sri Aman dari tahun 1980-2000 serta pandangan penduduk terhadap pembangunan bandar Sri Aman - Hiew, Lan Foon (University Malaysia Sarawak, UNIMAS., 2003)
The purpose of this research was to identify the development which occurred in Sri Aman town between the year 1980-2002 and the views of the local people on development in Sri Aman town. Besides, the research was also aimed at making research on the factors which attract and hinder development of Sri Aman town and analyze the effect of development on the local people.